AN ANALYSIS EFL STUDENTSANALYSIS EFL STUDENTS TRANSLATION OF PREPOSITION IN, ON AND AT A THINK ALOUD- PROTOCOL STUDY TRANSLATION OF PREPOSITION IN, ON AND AT A THINK ALOUD- PROTOCOL STUDY - wuriy handayani (LINGUA : JURNAL ILMIAH, 2019)
Translating prepositions in, on and at is not an easy job for EFL students since the meanings relate to locating object, time, and degree. With regard to this point, this study aims at identifying strategies, methods, and procedures used by EFL students to translate preposition in, on and at. Both quantitative and qualitative methods are applied in this study. Think-Aloud Protocol data collecting technique carries out to identify student’s strategies, methods, and procedures in translating prepositions in, on and at. To do this, the data of student’s transcriptions and students’ translations obtained from three students were analyzed. The findings indicate that students use more than one strategies, methods and procedures.